Energy cost and running mechanics during a treadmill run to voluntary exhaustion in humans - Candau, R.; Belli, A.; Millt, G. Y.; Georges, D.; Barbier, B.; Rouillon, J. D. (European Journal of Applied Physiology, 1998)
The aim of the present study was to examine the physiological and mechanical factors which may be concerned in the increase in energy cost during running in a fatigued state. A group of 15 trained triathletes ran on a treadmill at velocities corresponding to their personal records over 3000m [mean 4.53 (SD 0.28) m · s-1] until they felt exhausted. The changes in CR (energy cost of running) were linked (r = 0.77, P < 0.01) to the changes in the variability of step frequency and in the variability of potential cost suggesting that a large proportion of the increase in CR was due to an increase in the step variability.